Bee stressors from an immunological perspective and strategies to improve bee health - El-Seedi, Hesham R.; Ahmed, Hanan R.; Abd El-Wahed, Aida A.; Saeed, Aamer; Algethami, Ahmed F.; Attia, Nour F.; Guo, Zhiming; Musharraf, Syed G.; Khatib, Alfi; Alsharif, Sultan M.; Al Naggar, Yahya; Khalifa, Shaden A. M.; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Honeybees are the most prevalent insect pollinator species; they pollinate a wide range of crops. Colony collapse disorder (CCD), which is caused by a variety of biotic and abiotic factors, incurs high economic/ecological loss. Despite extensive research to identify and study the various ecological stressors such as microbial infections, exposure to pesticides, loss of habitat, and improper beekeeping practices that are claimed to cause these declines, the deep understanding of the observed losses of these important insects is still missing. Honeybees have an innate immune system, which includes physical barriers and cellular and humeral responses to defend against pathogens and parasites. Exposure to various stressors may affect this system and the health of individual bees and colonies. This review summarizes and discusses the composition of the honeybee immune system and the consequences of exposure to stressors, individually or in combinations, on honeybee immune competence. In addition, we discuss the relationship between bee nutrition and immunity. Nutrition and phytochemicals were highlighted as the factors with a high impact on honeybee immunity.